Ahmad Surkitti (1876-1943): his life, thought and Islamic reform Indonesia - Abu Shouk, Ahmed Ibrahim (2010)
Shaykh Ahmad Muhammad al-Surkitti (1876-1943) was an important figure in the Islamic reform movement in early twentieth-century Indonesia. He was born in the Sudan in 1876, studied in Makkah and Madina for fourteen years (1897-1911), and established his career as a school teacher and a celebrated reformist leader in Indonesia (1911-1943). The purpose of this research project is to examine the early life and career of al-Surkitti in the Sudan and Saudi Arabia, and assess critically his contribution to the islah and tajdid movements in the Malay-Indonesia world. His intellectual and religio-political discord and conflict with the Alawi traditionalists will be investigated in the context of Hahdarmi identity and discourse between 'orthodox Islam' propagated by Surkitti and his followers and 'popular Islam' that gave the Alawi sayyids special recognition in their home society in Hadramaut and Diaspora in Indonesia.